Peran Kepala Sekolah dalam Pelaksanaan Manajemen Berbasis Sekolah di SD Negeri 6 Banyuning - Riska Amilia; Kadek Anggi Lia Pinata; Ridolvina Unawekla; I Putu Krishna Aditya; Ida Ayu Ketut Raka Septiani; Ida Ayu Komang Rai Septiana (Asosiasi Dosen Muda Indonesia, 2025)
The purpose of this article is to examine the role of the principal in the implementation of school-based management. This study employs a qualitative method with a descriptive approach. The research was conducted at SD Negeri 6 Banyuning. Data collection techniques used in this study include interviews, field observations, and document studies. The aim of the research is to identify and describe the professionalism of the principal in implementing school-based management. Based on the findings in the field, the principal's role in implementing school-based management has been professional. The principal serves as a role model and motivator for both teaching and administrative staff. The researcher concludes that the principal has effectively carried out leadership roles, motivated teachers, and improved educational facilities and infrastructure in the implementation of school-based management. The researcher recommends that the principal continue to enhance their professionalism in fulfilling their role to ensure the institution's growing recognition and trust within the community.